UPAYA MENINGKATKAN KEPERCAYAAN PADA ORGANISASI MELALUI PERBAIKAN PERILAKU PEMIMPIN DAN KEADILAN ORGANISASI - Patras, Yuyun Elizabeth; Hidayat, Rais; Lian, Bukman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
Organizational trust is essential for members of the organization can continue to contribute the progress of the organization. The purpose of this research was to find out how far the variables of leadership behavior and organizational justice on improving organizational trust. The research method used is associative quantitative causal method, and the testing hypothesis research using path analysis technique. The population in this study is 707 permanent lecturers who have the National Lecturer Number (NIDN). The sample is 130 respondents. The instrument test was conducted to 30 respondents outside the sample. The findings of this research indicate that the higher leadership behavior in directing subordinates, providing support to subordinates; increase member participation in achieving organizational goals, and rewarding the achievers, will significantly higher the trust in the organization. Other finding showed that the higher organizational justice will close to the higher of the trust in the organization